The Patient's Fulfillment with Removable Partial Denture Treatment from Point of The Consolation and Mastication - Hussein Abuzgyaia (AlQalam Journal of Medical and Applied Sciences, 2022)
Aims. The purpose of this article was to determine if there was a relationship between removable partial dentures satisfaction and efficiency of mastication in patients with partial dentures. Methods. A total of 40 people with removable partial dentures, ranging in the age from 25 to 66, were evaluated. After the dentures were construction and insertion, patients were interviewed about their comfort and mastication efficiency, and rate their satisfaction on a scale of 1 to 5. Results. In comparison to male patients, the majority of females (57 %) were satisfied with the comfort of their dentures, with differences significant between the two groups. About efficiency of mastication, the male patients had the highest satisfaction rate (54%) compared to the female patients. When comparing age groupings, the group I satisfy had the highest percentage compared to the group II. Female patients were more satisfied with their dentures than male patients, and group II they were more satisfied than group I patients in comfort. Conclusion. When it came to efficiency of mastication, male patients were more satisfied than female patients, and age of patients, the group I satisfied the most people compared to the group II.